How Workspaces Influence Software Development? Preliminary Results of a Systematic Literature Review - G. J. Costa, Victor; França, Cesár (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM), 2019)
This work brings to light the preliminary results of a literature review showing what physical elements of workspaces have been studied in software engineering, and what are their known impacts on software development performance. A systematic literature review has been conducted, covering a period of 16 years of publications in software engineering field. Seven dimensions of workspace factors were mapped and we present the impacts of these factors on elements of software development performance, such as communication and collaboration. This article evidences the fact that there is not a generally accepted best model for software development workspaces, and that there is still much room for investigation in this topic